The Effect of the TOEFL Preparation Program on Reading Skills and Structure Mastery of Prospective Students - Pranoto, Yohanes Heri (JET ADI BUANA, 2020)
Preparation is one step for someone to be mentally feasible and skilful to join and be a part of an activity or a group. Likewise is for senior high school students proposing to go to higher education. One challenge for those prospective university students is the mastery of English - a scientific language. The study aims at assisting the prospective students, at the level of pre-intermediate English skills, ready to continue to higher education by providing an English reading and structure course. The participants are 14 final-level students of St. Paul Minor Seminary. One-group experiment design, with pre-posttest design, is used to perceive the effectiveness of the course. The findings show the improvement only on reading skills. However, the test-result discussion on the structure is held to observe the washback effect on the test performance. The test questions are taken from the English Proficiency Test of Musi Charitas Catholic University.